Rapid Screening of Peptide Probes through In Situ Single-Bead Sequencing Microarray - Wang, Weizhi; Wei, Zewen; Zhang, Di; Ma, Huailei; Wang, Zihua; Bu, Xiangli; Li, Menglin; Geng, Lingling; Lausted, Christopher; Hood, Leroy; Fang, Qiaojun; Wang, Hao; et al. (Analytical chemistry (Washington), 2014)
Peptide ligands as targeting probes for in vivo imaging and drug delivery have attracted great interest in the biomedical community. However, high affinity and specificity screening of large peptide libraries remains a tedious process. Here, we report a continuous-flow microfluidic method for one-bead–one-compound (OBOC) combinatorial peptide library screening. We screened a library with 2 × 105 peptide beads within 4 h and discovered 140 noncanonical peptide hits targeting the tumor marker, aminopeptidase N (APN). Using the Clustal algorithm, we identified the conserved sequence Tyr-XX-Tyr in the N terminal. We demonstrated that the novel sequence YVEYHLC peptides have both nanomolar affinity and high specificity for APN in ex vivo and in vivo models. We envision that the successful demonstration of this integrated novel nanotechnology for peptide screening and identification open a new avenue for rapid discovery of new peptide-based reagents for disease diagnostics and therapeutics.